2019
DOI: 10.1364/oe.27.031207
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic photoluminescence properties of individual micro-particle of Cs4PbBr6 perovskite with “defect” structure

Abstract: Optical performance of the lead halide perovskites with zero-dimension (0D) structure has been in a hot debate for optoelectronic applications. Here, Cs 4 PbBr 6 hexagonal micro-particles with a remarkable green emission are first fabricated via a low-temperature solution-process employed ethanol as solvent. Our results underline that the existence of bromine vacancies and the introduction of hydroxyl induce a narrowed band gap with the formation of a defect level, which contributes to the extrinsic photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…[38] The second theory involving a vacancy-assisted PL emission was offered, which regarded the strong PL emission as due to the intrinsic nature of Cs 4 PbBr 6 , in which Br vacancies (in most cases), tribromide and interstitial hydroxyl served as radiative recombination centers. [32,[39][40][41][42][43][44][45] From DFT calculation results, it was found that i) Br vacancies had a small formation energy under Br-deficit conditions; ii) their transition level matched well with the emissive energy; iii) their electronic charge density was highly localized (Figure 3a,b). [29] Therefore, one could obtain Cs 4 PbBr 6 with stronger PL emission if more defects could be induced under extremely Br-poor conditions.…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] The second theory involving a vacancy-assisted PL emission was offered, which regarded the strong PL emission as due to the intrinsic nature of Cs 4 PbBr 6 , in which Br vacancies (in most cases), tribromide and interstitial hydroxyl served as radiative recombination centers. [32,[39][40][41][42][43][44][45] From DFT calculation results, it was found that i) Br vacancies had a small formation energy under Br-deficit conditions; ii) their transition level matched well with the emissive energy; iii) their electronic charge density was highly localized (Figure 3a,b). [29] Therefore, one could obtain Cs 4 PbBr 6 with stronger PL emission if more defects could be induced under extremely Br-poor conditions.…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 99%
“…However, to the best of our knowledge, we did not find any formula to follow. For Cs 4 PbBr 6 , the synthesis could be performed with a CsBr/PbBr 2 ratio ranging from 1:4, [42] 1:2, [89] 1:1, [38,44,49,57,86,94] 2:1, [85,88] 3:1 [87] to 4:1. [95] In the production of CsPb 2 X 5 , the CsX/PbX 2 ratio could be one of 1:10, [96] 1:5, [88] 1:3, [59] 1:2.5, [67] 1:2, [97] 1:1.…”
Section: Antisolvent Re-precipitationmentioning
confidence: 99%
“…The other strong opinion proposes that the green luminescence is due to point defects in Cs 4 PbBr 6 structure. Some possible defects that may cause green luminescence were identified, for example the Br vacancy [ 40 , 41 , 42 ]. For more details, please refer to review papers published on this subject, for example the most recent, [ 28 ], which supports the opinion based on the presence of nanoinclusions, and provides persuasive arguments rebutting the Br vacancy concept.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported by Yang et al also support the defect mechanism, but offer yet another reason for green emission. 71 In this case, Cs 4 PbBr 6 micro-particles were synthesized involving ethanol as a polar solvent. Assisted by DFT calculations, they infer that the impact of the OH- group (presumably from ethanol) was to reduce the band gap of the Cs 4 PbBr 6 host from 3.75 eV to 3.5 eV, also downshifting the Br-vacancy level from 2.75 eV to 2.44 eV, which approximately matches with the ∼520 nm green emission.…”
Section: Br-vacancy or Similar Defectsmentioning
confidence: 99%